Rebellions, Revolts, and Uprisings in the Metropolis of Cordoba during the Almoravids Era (500 – 541 AH / 1106 – 1146) - Chaki , Abdelaziz (The Algerian Historical Journal, 2026)
This research presents the most significant rebellions, revolts, and uprisings that the metropolis of Córdoba experienced during the final four decades of the Almoravids (500 – 541 AH / 1106 – 1146). This opposition movement against the Almoravids ’authority varied according to its motives and causes. Sometimes, it was led by Almoravids’ leaders, such as the governor of Córdoba, who refused to pledge allegiance to the new Emir Ali ibn Yusuf. At other times, it was led by religious scholars, such as Ibn Hamdin, who was initially among the loyalist scholars but later opposed the authority and urged scholars to revolt in other Andalusian cities. While these revolts occasionally emerged as collective popular movements without a specific leader, their underlying causes varied in each instance. Sometimes, they aligned with the ambitions of their instigators; other times, they arose as reactions to the excesses of the ruling authority and its institutions, the actions of the Jewish community in response to alleged crimes, or harsh natural circumstances such as famine and plague. The official authorities' handling of these revolts ranged from leniency and tolerance at times, yielding to the demands of the protesters at other times, to suppression and the use of force on yet other occasions.